2013
DOI: 10.1002/jctb.4025
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of beet molasses as the fermentation substrate for industrial vitamin B12 production by Pseudomonas denitrificans

Abstract: BACKGROUND: Fermentation of the industrial vitamin B 12 by Pseudomonas denitrificans usually utilizes sucrose or maltose as the sole carbon source, which results in increased medium costs. In order to decrease the fermentation cost, it is crucial and essential to employ a low-cost and convenient raw material as an alternative medium substrate for industrial vitamin B 12 production. RESULTS:The results obtained in chemically defined medium showed that glutamate and sucrose were favorable for cell growth and vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…According to the above results, it could be concluded that betaine metabolism would accompanied by large generation of glycine. Using the synthetic medium, our previous study had been clearly illustrated that glycine in fermentation broth would impose a severe restriction on the cell growth of P. denitrificans [11]. Thus, the highly vast amounts of generated extracellular glycine attributed to the actual reason why the cell growth rate under 10 g/l betaine was dramatically lower than that in the case of betaine absence (as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…According to the above results, it could be concluded that betaine metabolism would accompanied by large generation of glycine. Using the synthetic medium, our previous study had been clearly illustrated that glycine in fermentation broth would impose a severe restriction on the cell growth of P. denitrificans [11]. Thus, the highly vast amounts of generated extracellular glycine attributed to the actual reason why the cell growth rate under 10 g/l betaine was dramatically lower than that in the case of betaine absence (as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“… 6 , 17 , 18 Molasses, the major and most valuable byproduct of beet sugar refining, has been the principal source of natural betaine. 19 21 Vinasse, a byproduct of ethanol fermentation of molasses, is another important source of betaine.…”
Section: Introductionmentioning
confidence: 99%
“…These substrates are available in huge amounts, have very low added values, but are nutrient-rich for microbial growth (carbohydrates, proteins, and minerals). [13][14][15][16] One residue of particular interest in this case is the liquid acid protein residue of soybean (LAPRS), which is obtained as an effluent during the soybean-isolated protein process (SIP). For instance, one single industrial facility for SIP production generates approximately 50,000 m 3 of LAPRS monthly.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting factor regarding the use of this microorganism is the possibility of producing vitamin B12 using alternative culture media composed of agroindustry residues. These substrates are available in huge amounts, have very low added values, but are nutrient‐rich for microbial growth (carbohydrates, proteins, and minerals) 13‐16 . One residue of particular interest in this case is the liquid acid protein residue of soybean (LAPRS), which is obtained as an effluent during the soybean‐isolated protein process (SIP).…”
Section: Introductionmentioning
confidence: 99%